Hard-core magnons in the S=1/2 Heisenberg model on the square lattice - Schmidt, Kai Phillip; et al. (Physical Review B, 2006)
We propose a versatile approach to treat commonly arising constraints. It is illustrated for interacting magnons of the Heisenberg antiferromagnet on a square lattice. For systems of LxL sites a nonperturbative continuous unitary transformation (CUT) is used to derive an effective Hamiltonian conserving the number of magnons. They are bosonic particles with a hard-core constraint which is captured by a local, repulsive interaction U. The limits U ->infinity and L ->infinity are achieved by extrapolation. The residual spin gap Delta(1) is smaller than 0.01J reflecting the gapless nature of the magnons. The one-magnon dispersion displays all known characteristics.